The Effect of Practicum-Based Learning on Elementary Students’ Achievement in Magnetism - Dila, Afifah Sellen; Shalihah, Siti; Khairunnisa, Khairunnisa; Hasanah, Mila (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study empirically examines the instructional effectiveness of the practicum method on the learning achievement of Grade 5 students in Integrated Science and Social Studies (IPAS), with a focus on the topic of magnetism at MIS Muhammadiyah 3 Al-Furqan. Conventional IPAS instruction remains largely teacher-centered, limiting students' understanding of abstract scientific concepts. To address this issue, the study implemented a practicum-based learning approach. A quantitative quasi-experimental design with a nonequivalent control group was employed, involving 52 fifth-grade students divided into an experimental class and a control class. Learning outcomes were measured using pretest and posttest instruments and analyzed using an independent samples t-test. The results showed that the experimental class achieved significantly higher posttest scores (M = 77.62) than the control class (M = 66.19) (p = 0.004). The effect size analysis revealed a significant practical effect of the practicum method on learning achievement (Cohen's d = 0.84), indicating strong pedagogical significance. This study provides empirical evidence supporting the integration of practicum-based learning to enhance elementary IPAS instruction within the madrasah ibtidaiyah context.